2011
DOI: 10.1002/elsc.201000190
|View full text |Cite
|
Sign up to set email alerts
|

Linking ecology with economy: Insights into polyhydroxyalkanoate‐producing microorganisms

Abstract: Polyhydroxyalkanoates (PHA) constitute a group of microbial biopolyesters with important ecosystem functions and a high biotechnological potential. During the past decade, the rapid development of new molecular and microscopic techniques resulted in novel insights into the ecology of PHA‐producing bacteria in aquatic and terrestrial microenvironments. Ecosystems showing fluctuating availability of carbon or transient limitation of essential nutrients, e.g. the rhizosphere of plants or estuarine sediments, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(71 citation statements)
references
References 106 publications
0
69
0
Order By: Relevance
“…The regulation of PHA production may be directly linked to biofilm formation (Campisano et al 2008, Tribelli et al 2012. PHA-producing bacteria in marine habitats have so far been mostly found in sediments or biofilms (Koller et al 2011), although 2 species of the genus Oceanicola (Alphaproteobacteria), isolated from seawater at the Bermuda-Atlantic Time-series Study Site, have been shown to produce intracellular PHA granules in culture (Cho & Giovannoni 2004). We found various bacterial morphotypes containing putative PHA granules in the bottom ice samples (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…The regulation of PHA production may be directly linked to biofilm formation (Campisano et al 2008, Tribelli et al 2012. PHA-producing bacteria in marine habitats have so far been mostly found in sediments or biofilms (Koller et al 2011), although 2 species of the genus Oceanicola (Alphaproteobacteria), isolated from seawater at the Bermuda-Atlantic Time-series Study Site, have been shown to produce intracellular PHA granules in culture (Cho & Giovannoni 2004). We found various bacterial morphotypes containing putative PHA granules in the bottom ice samples (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…For example, PHB from Gram-negative organisms are widely used in a variety of products but due to endotoxin in the outer membrane lipopolysaccharides (LPS), Bacillus species which lack LPS are extensively used in biopharmaceutical applications (70) but compared to Gram-negative bacteria, Gram-positive bacteria were mostly found to produce scl-PHA and at lower PHA contents between about 2% and 50% CDM, that is why Gram-positive bacteria have yet to be adopted for commercial PHA production (58). Further, Koller et al have suggested to link ecology with economy, because bacteria residing at ecological niches like estuarine sediments, marine microbial mats, rhizosphere, groundwater sediments and engineered ecosystems with fluctuating nutrient contents support the population actively involved in PHA accumulation to meet the metabolic energy requirements during starvation period and this concept can be implemented industrially to reduce the cost of biopolymers commercially with sustainable production processes (268). Therefore, it is economical to use naturally producing microorganism due to safety and constant productivity rate, and there is great potential for producing PHAs in low-cost substrates, which can reduce PHAs production costs, because the cost of substrate is the most important factor for PHAs production (269)(270)(271).…”
Section: Economical Aspectsmentioning
confidence: 99%
“…PHA accumulation is one of the stress-driven responses experienced by microbes residing at different ecological niches such as estuarine sediments, marine habitat, rhizospheric soil, groundwater sediments and sewage. These environments are frequently rich in organic contents and possess minimum nutrients for supporting PHB accumulation and metabolic energy requirements during starvation period [4]. More specifically, waste and wastewaters has high BOD and COD values as compared to other ecological niches to support growth of these microbes by utilizing the nutrients present in wastewater and converting them into valuable PHAs that can be used as polymers [5].…”
Section: Introductionmentioning
confidence: 99%